Effect of Processing Variables on Anthocyanin and Total Polyphenol Extraction from Water Caltrop (Trapa bispinosa) Hull - Adhikari, Babita; Shrestha, Ojeswi Krishna (Himalayan Journal of Science and Technology, 2018)
Anthocyanins are water soluble pigments responsible for the brilliant orange red through deep purple colors in flower and fruits. The effects of different extraction variables (pH, particle size, temperature and time, extraction method) on anthocynin, total polyphenol content and antioxidant of the extracts were studied. The anthocyanin content of fresh and dried (55 °C for 2 h) water caltrop hull were 68.68 and 44.38 μg/100 g d.b. respectively. Temperature, particle size and pH played a significant role (p